Early Childhood Naturalist Intelligence Through Animal Sounds in Audiobooks What is That Sound? “Meilania's Novel Work” - Dulasa, Mardiyah (International Proceedings of Nusantara Raya, 2024)
Novel Meilania. Naturalist intelligence, which relates to the ability to recognize and interact with the natural environment, is essential to the foundation of a child's understanding of the world around them. The book is designed with interesting illustrations and interactive elements, and includes animal sounds that are accessible to children. Through this approach, the article explains its benefits in improving cognitive abilities, language, and a sense of empathy for the environment. Thus, this book becomes an effective means to stimulate naturalist intelligence and create a fun learning experience for children.